PERSEPSI MASYARAKAT INTERNASIONAL TERHADAP CITRA NEGARA QATAR MELALUI PIALA DUNIA 2022 - Putri Kalih Nuraida, (2023)
The FIFA World Cup 2022 provides an opportunity for Qatar to showcase its image to the international community. This research is based on the significance of a country's image as a factor that influences international relations. The study also explores the international public's perception of Qatar's image through the FIFA World Cup 2022. The authors analyze using the concepts of perception and public opinion, employing research methods such as Twitter crawling, interviews with volunteers and visitors, and analysis of international media coverage, which reveals diverse perceptions of Qatar's image, with the majority expressing positive or neutral sentiments. The interviews and media analysis provide a broad perspective on Qatar's image. The findings of this research indicate a shift from negative to positive responses towards Qatar's image as the FIFA World Cup 2022 progresses.